Predicting The Residual Performance Resource of Pneumatic Tires - Maxmudjon, Melibayev; Anvar, Dadaxodjaev; Mahmudjanovich, Mamadjanov (Journal of Mechanical Engineering, 2025)
This study aims to predict the residual performance resource of pneumatic tires used in agricultural machinery, particularly tractors, to optimize their lifespan and maintenance strategies. Understanding the durability and wear characteristics of pneumatic tires is essential for ensuring efficiency and reducing unexpected failures. The research employs static and dynamic prediction methods to estimate the remaining service life of tractor tires. The static prediction assumes a linear degradation over time, while the dynamic prediction incorporates periodic evaluations of tire conditions, allowing for more precise estimations. The study follows ISO 13381-1:2015 standards for machine condition monitoring and diagnostics, integrating statistical models and probability analysis to assess failure rates and maintenance schedules. The results indicate that dynamic prediction provides a more accurate assessment of residual tire life compared to static methods. The study also finds that proper monitoring can significantly extend the operational lifespan of tractor tires, reducing maintenance costs and minimizing machine downtime. With a 95% confidence level, the research confirms that effective diagnostics and predictive maintenance strategies enhance the reliability and efficiency of agricultural machinery.